2010
DOI: 10.1162/jocn.2009.21300
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Integration in Visual Word Recognition

Abstract: Abstract■ When two displays are presented in close temporal succession at the same location, how does the brain assign them to one versus two conscious percepts? We investigate this issue using a novel reading paradigm in which the odd and even letters of a string are presented alternatively at a variable rate. The results reveal a window of temporal integration during reading, with a nonlinear boundary around ∼80 msec of presentation duration. Below this limit, the oscillating stimulus is easily fused into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 62 publications
(103 reference statements)
2
16
0
Order By: Relevance
“…The information persistence lasted for at least 200 ms. At longer intervals the two-flash models did not drop all the way to the one-flash baseline, which could reflect the contribution of information that has been stored in working memory intervals may be quite different where the observer must synthesize across groups of complete letters in order to perceive a word. Forget et al (2010) flashed two three-letter components of a six-letter word, e.g., B_A_N_ and _R_I_S to form BRAINS. They found effective two-pulse summation that allowed recognition of the whole word out to 80 ms.…”
Section: Information Persistence In Iconic and Working Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…The information persistence lasted for at least 200 ms. At longer intervals the two-flash models did not drop all the way to the one-flash baseline, which could reflect the contribution of information that has been stored in working memory intervals may be quite different where the observer must synthesize across groups of complete letters in order to perceive a word. Forget et al (2010) flashed two three-letter components of a six-letter word, e.g., B_A_N_ and _R_I_S to form BRAINS. They found effective two-pulse summation that allowed recognition of the whole word out to 80 ms.…”
Section: Information Persistence In Iconic and Working Memorymentioning
confidence: 99%
“…Stimulus information was integrated only under limited task conditions (Brockmole et al 2002;Jiang et al 2005). Busey (1998) provided quantitative modeling of inhibitory interactions with successive displays of digits, and Forget et al (2010) found competition in the perception of trigrams.…”
Section: Information Persistence In Iconic and Working Memorymentioning
confidence: 99%
“…During reading, the VWFA is thought to play a key role in processing all of a word's letters in a parallel rather than serial fashion (Dehaene et al, 2005;Forget et al, 2009). Expert readers show essentially constant naming times, regardless of the number of letters in a word, at least below~8 letters (Cohen et al, 2008;Lavidor and Ellis, 2002).…”
Section: Parsing Of Mathematical Expressions In Ventral Visual Cortexmentioning
confidence: 99%
“…Reilhac et al, 2013) prior to their mapping to phonemes. However, the visual operation of spatial attention is distinct from GPC mapping: In the DRC model, all letters are hypothesized to be activated simultaneously (a view supported by recent behavioral and neural findings: Adelman, Marquis, & Sabatos-DeVito, 2010;Forget, Buiatti, & Dehaene, 2010).…”
Section: Dorsal Parietal Cortexmentioning
confidence: 99%